The Role of Pre-Marital Counselling by BP4 in Realising a Sakinah, Mawaddah, and Warahmah Family - muhammad kholis qolbi; Ikhwan Hamdani; Syarifah Gustiawati Mukri (IBN KHALDUN BOGOR, 2025)
The high rate of divorce in Indonesia, including in Ciomas Subdistrict, Bogor Regency, indicates weak family resilience, largely caused by couples’ lack of understanding regarding the essence and purpose of marriage. From an Islamic perspective, marriage is a sacred institution aimed at forming a family that embodies tranquility (sakinnah), affection (mawaddah), and compassion (rahmah), commonly referred to as SAMAWA. Therefore, implementing structured pre-marital counseling is essential. This study aims to examine the role of the Advisory Board for the Development and Preservation of Marriage (BP4) under the Religious Affairs Office (KUA) of Ciomas in providing pre-marital guidance, and to evaluate the effectiveness of the program in preparing prospective spouses to enter a harmonious family life. This research adopts a mixed methods approach, combining qualitative and quantitative techniques. Data collection involved semi-structured interviews with BP4 officers, direct observation of counseling sessions, document analysis, and the distribution of pre-test and post-test questionnaires to 51 respondents (102 prospective brides and grooms). The findings show that BP4 actively delivers guidance materials encompassing psychological, social, and religious aspects. The comparison of pre-test and post-test data indicates a significant improvement in participants’ readiness for marriage. However, the program still faces several challenges, including low participant attendance, limited human and material resources, and the absence of effective post-guidance follow-up. Therefore, strengthening and optimizing the implementation of pre-marital counseling is necessary to ensure BP4 can fulfill its role effectively in preventing divorce and fostering SAMAWA families. Keywords: Pre-marital guidance; BP4; Sakinah Mawaddah Warahmah (SAMAWA) family